Design of gas-liquid two-phase separation device with application in solar hydrogen production system - Geng, Boxi; Guene Lougou, Bachirou; Shuai, Yong; Zhang, Hao; Pan, Qinghui; Han, Dongmei; Jiang, Boshu; Wu, Lianxuan; Wang, Ziyue (Renewable & sustainable energy reviews, 2023)
Currently, solar thermochemical energy conversion technology has attracted more and more attention because of the increasing global need for clean fuel and chemical energy demand. The thermochemical hydrogen production technology uses solar radiation with concentrated high-density as a high-temperature heat source to produce hydrogen by decomposing water through two-step cycle redox reactions. It is an environment-friendly technology based on artificial photosynthesis utilizing water vapor as the reaction gas. However, limited by the separation efficiency, current gas-liquid separation devices cannot output stable high-purity water vapor and sophisticate the experimental processes. In this research, intensive numerical investigations were carried out on the widely-used corrugated plate steam separators. The structural parameters are designed by the multi-objective optimization method combining the artificial neural network and the genetic algorithm. Nine optimized structures are designed by adding hydrophobic hooks, streamlined, and reducing the plate distance optimization methods. The results give engineering application conditions of different optimized separators. The streamlined single-hook corrugated plate separator with rounded corners exhibited the best separation efficiency under the heat state condition, which is 97.27%. It can also completely separate droplets over 28.5 μm. The applicability of the cyclone steam separators indicated that it is more suitable for pretreatment. The benchmark experimental system was built for the measurement of the separation efficiency resulting in only a 0.73% error. The designed steam separator was successfully applied to the solar thermochemical hydrogen production experiment, which ensures its practicability and pertinence in the process of solar fuel synthesis. [Display omitted] •Compact steam separation device is designed for solar hydrogen production system.•Structural parameters are determined via a multi-objective optimization method.•Steam separator with optimized structure revealed a separation efficiency of 98.01%.•Applicability of nine different kinds of steam separators was demonstrated.•High efficiency of the steam separator ensures the stability of hydrogen yield.